On Polynomials of the Form xrf(x(q−1)/l) - Amir Akbary; Qiang Wang (International Journal of Mathematics and Mathematical Sciences)
We give a general criterion for permutation polynomials of the form xrf(x(q−1)/l), where r≥1, l≥1 and l∣(q−1). We employ this criterion to characterize several classes of permutation polynomials.